2013
DOI: 10.4049/jimmunol.1200780
|View full text |Cite
|
Sign up to set email alerts
|

TLR7 Stimulation of APCs Results in Inhibition of IL-5 through Type I IFN and Notch Signaling Pathways in Human Peripheral Blood Mononuclear Cells

Abstract: TLR7 agonists modulate Th2 immune responses through mechanisms that have not been fully elucidated. Suppression of IL-5 production from Ag- or phytohemagglutinin-stimulated human PBMCs by the TLR7 antedrug AZ12441970 was mediated via type I IFN–dependent and type I IFN–independent mechanisms through TLR7 activation of plasmacytoid dendritic cells, B cells, and monocytes. The type I IFN–dependent inhibition of T cell–derived IL-5 was mediated by IFN-α acting directly on activated T cells. IL-10 was shown not to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 46 publications
(67 reference statements)
2
17
0
Order By: Relevance
“…28 Our results suggest a reciprocal regulation between IL-5-induced eosinophilia and TLR7 expression that affects antiviral IFN responses to RV (summary illustrated in figure 5). In the absence of virus, it has been shown that TLR7 stimulation with synthetic agonists in vitro resulted in inhibition of IL-5 through IFNγ and Notch signalling pathways in antigenpresenting cells 29 and upregulation of IFNγ production by memory CD4+ T cells 30 and natural killer cells. 31 Consistent with these findings, we show impaired IFNγ release in the absence of TLR7 promotes T H 2 immune responses, which can be rescued by type I and III IFN therapy or adoptive transfer of TLR7-sufficient pDCs.…”
Section: Discussionmentioning
confidence: 99%
“…28 Our results suggest a reciprocal regulation between IL-5-induced eosinophilia and TLR7 expression that affects antiviral IFN responses to RV (summary illustrated in figure 5). In the absence of virus, it has been shown that TLR7 stimulation with synthetic agonists in vitro resulted in inhibition of IL-5 through IFNγ and Notch signalling pathways in antigenpresenting cells 29 and upregulation of IFNγ production by memory CD4+ T cells 30 and natural killer cells. 31 Consistent with these findings, we show impaired IFNγ release in the absence of TLR7 promotes T H 2 immune responses, which can be rescued by type I and III IFN therapy or adoptive transfer of TLR7-sufficient pDCs.…”
Section: Discussionmentioning
confidence: 99%
“…The presenilin/γ-secretase (PS/γS) proteolysis of CD46 generates immunoprecipitable cytoplasmic tail peptides (cyt1/2) in response to Neisseria infection (Weyand et al, 2010). However, blocking Notch signaling by γ-secretase inhibitors has been found to reduce the type I IFN-independent suppression of IL-5 in human peripheral blood mononuclear cells, indicating that Notch signaling can inhibit IL-5 (Edwards et al, 2013).…”
Section: Cd46mentioning
confidence: 97%
“…TLR7 agonists suppress Th2 responses [9][10][11][12][13][14][15][16] and as atopic asthma is associated with an enhanced Th2 biological drive, TLR7 agonists could be developed as a new treatment paradigm for this disease. However, the generation of 'influenza-like' symptoms resulting from either systemic TLR7 activation or elevated systemic levels of TLR7-induced mediators has been reported in TLR7 clinical programmes.…”
Section: Discussionmentioning
confidence: 99%
“…18 Peripheral blood mononuclear cell (PBMC) preparation and IL-5 inhibition assays are as described in Edwards et al's study. 15 IFNα was determined following a 24 h incubation of PBMC with compound. In vitro plasma stability determinations were performed by methodologies described in Biffen et al's study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation